Future skill needs in Europe: medium-term forecast : background technical report - (:unkn) unknown (Publications Office of the European Union, 2009)
"This publication provides a detailed technical background and reviews the first skill demand forecast in Europe. It outlines the approach and methods adopted and presents the results for Europe as a whole (EU-25, Norway and Switzerland) as well as for individual countries. It also untangles many data and technical issues and sets out the solutions that were adopted. The overall aim is to develop a comprehensive system for producing detailed and consistent quantitative projections of future skill needs across Europe. This approach and the set of results provide a sound foundation to take the debate on the changing pattern of demand for skills forward." (Herausgeber, BIBB-Doku)
Keywords: G 1.2.3.2 Anforderungen & Bedarfe; G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; T 1.5 International vergleichende Berufsbildungsforschung; I 2.2 Europa; Qualifikationsbedarf; Früherkennung; Beschäftigungsentwicklung; Wirtschaftszweig; Fachkräftemangel; Prognose; Szenario; Europäische Union; Norwegen; Schweiz; Quantitative Angaben; 2006-2015